Synergetic approach in pedagogy as a platform for studing the phenomenon of personal self-development - Таубаева, Шаркуль (Pedagogy and Psychology, 2020)
This article expands the boundaries of pedagogical science and innovative didactics by considering their capabilities from a new interesting and multi-faceted position of the synergetic approach. The synergetic approach has a calasal potential that makes it possible to integrate multi-faceted areas of synergetics for the development of innovative didactics, which is based on assistance in self-development and self-education of students. Synergetics allows innovative didactics to explain the directions of its development from the perspective of requirements and changes in education, as well as to justify the conceptual foundations of its new positions and the use of innovative technologies in the educational process for adult students. The synergetic approach justifies the possibilities of the trajectory of self-development and self-education from the perspective of the individual and its diverse and branched orientation with changing orders and desires. The publication was prepared as part of the applied grant research for 2020-2022 commissioned by the Ministry of education and science of the Republic of Kazakhstan on the topic «Synergetic foundations and euthantics for self-development of spiritual and moral qualities» of the IRN AP08856223.